(untitled) (Nigerian Journal of Pharmaceutical Research, 2023)
Backgroud: Direct leaf extracts of Dissotis rotundifolia are commonly used in rural settings including Abakaliki, Ebonyi State, Nigeria as traditional medicine for the treatment of eye injury and related diseases with limited information on the scientific basis of the microbiological quality/safety of the extract. Objective: This study investigated the microbial quality, antimicrobial effects of D. rotundifolia direct leaf extract. Materials and Methods: The extracts were evaluated for microbial contamination and stored for 5 days with daily screening for microbial quality. Antimicrobial test was assessed by agar diffusion at various concentrations against five clinical isolates namely; Staphylococcus aureus, Streptococcus pneumoniae, Pseudomonas aeruginosa, Citrobacter freundii and Candida species. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were also determined. Results: The findings of the study showed that D. rotundifolia fresh direct extract was not contaminated by any pathogenic bacteria or fungi until after 2 days of storage. The fresh extract was significantly (p < 0.05) more contaminated with Aspergillus flavus (20%) and Aspergillus niger (80%), whereas Aspergillus niger was the only contaminant in the dry extract up to 5 days of storage. The extract significantly (< 0.05) inhibited the growth of all test organisms with zone of inhibition varying between 4mm (S. Pneumoniae) to 15mm (Candida species). MIC for Candida species was observed at 500mg/ml and 200mg/ml for other test organisms while MBC was 500mg/ml for other test organisms Conclusions: The findings of this study are supportive of the use of D. rotundifolia extract in the treatment of bacterial-related ocular diseases and inflammation.